Prevalence of surgical site infections and their sensitivity patterns in elective abdominal surgeries in King George Hospital, Visakhapatnam - Ramani, Pratha Anantha; Kiran, Simhadri Uday; Deevi, Murali Manohar; Reddy, Ginni Vijay Sainath; Saichand, Ginjupalli; Yeeli, Sivaram Shashank; Reddy, Potireddy Yaswanth (International Surgery Journal, 2020)
Background: Surgical site infections are one of the most common complications in the postoperative period leading to increased morbidity, prolonged hospital stay and reduced quality of life. The present study aims to identify the incidence of surgical site infection (SSI), risk factors, causative organisms, and their sensitivity patterns in patients who have undergone elective abdominal surgeries. Methods: A prospective study containing 200 patients who have undergone elective abdominal surgeries from May 2018 to January 2020 were evaluated. A thorough history was taken in all the patients. A detailed clinical examination and routine investigations were done. Parameters such as body mass index (BMI), diabetic status, type of surgery, wound grading, culture, and sensitivity patterns were considered. The patients underwent treatment based on their investigatory reports. Results: In the present study, 54 patients developed surgical site infection, and among them, 22 are diabetics. Only ten patients with normal BMI developed SSI, whereas the other 44 patients who developed SSI had abnormal BMI. The incidence of SSI was higher in clean-contaminated surgeries comprising up to 89% of cases. Staphylococcus aureus was the most commonly isolated organism, and cefoperazone plus sulbactam was the most sensitive on antibiogram. Conclusions: The surgical site infections are on rising trend due to the emergence of antibiotic-resistant microorganisms. Treatment of the underlying risk factors, regular wound dressings, and antibiotics, according to sensitivity patterns, are the mainstay.